Agricultural inputs subsidy and their developmental impact: Conventional wisdom - Takeshima, Hiroyuki; Lee, Hak Lim (International Food Policy Research Institute, 2012)
An input subsidy program needs to be formulated and implemented with a good understanding of the following issues: What are the strategic development objectives that the subsidy program is to achieve? These objectives could include boosting food production through increased use of inputs, reducing poverty among smallholders through reduced costs of inputs, developing a private input‐supply network, improving soil nutrients, or some other goal altogether. What are the economic characteristics of the agricultural inputs to be subsidized? Will demand for inputs be expected to increase when the inputs are offered at a subsidized price? Is there sufficient supply capacity for meeting such increased demand?